Flexibility Is Costly: Hidden Physiological Damage From Seasonal Phenotypic Transitions in Heterothermic Species - Landes, Julie; Pavard, Samuel; Henry, Pierre-Yves; Terrien, Jérémy (Frontiers in Physiology, 2020)
Heterothermy allows organisms to cope with fluctuating environmental conditions. The use of regulated hypometabolism allows seasonal heterothermic species to cope with annual resource shortages and thus to maximize survival during the unfavorable season. This comes with deep physiological remodeling at each seasonal transition to allow the organism to adjust to the changing environment. In the wild, this adaptation is highly beneficial and largely overcomes potential costs. However, researchers recently proposed that it might also generate both ecological and physiological costs for the organism. Here, we propose new perspectives to be considered when analyzing adaptation to seasonality, in particular considering these costs. We propose a list of putative costs, including DNA damage, inflammatory response to fat load, brain and cognitive defects, digestive malfunction and immunodeficiency, that should receive more attention in future research on physiological seasonality. These costs may only be marginal at each transition event but accumulate over time and therefore emerge with age. In this context, studies in captivity, where we have access to aging individuals with limited extrinsic mortality (e.g., predation), could be highly valuable to experimentally assess the costs of physiological flexibility. Finally, we offer new perspectives, which should be included in demographic models, on how the adaptive value of physiological flexibility could be altered in the future in the context of global warming.